EFFICACY EVALUATION OF SPIROMESIFEN AGAINST RED SPIDER MITE, TETRANYCHUS URTICAE KOCH ON PARTHENOCARPIC CUCUMBER UNDER PROTECTED ENVIRONMENT - A. K. SOOD; SOMALI SOOD; VINAY SINGH (The Bioscan, 2015)
Novel acaricide, spiromesifen was evaluated at 96, 120 and 144 g ai/ha with standard acaricides namely, dicofol and propargite against Tetranychus urticae Koch on parthenocarpic cucumber under naturally ventilated polyhouse conditions. Application of spiromesifen 240 SC @ 144g a.i. /ha significantly reduced red spider mite infestation when sprayed at 21 days interval and was most efficacious in reducing mite population. Spiromesifen 240 SC @ 144g a.i. /ha also resulted in highest yield per plant. It was followed by dicofol and propargite. Phytotoxicity observations of spiromesifen recorded upto 15 days after application revealed no phytotoxicity symptoms at evaluated doses of 120, 144, 288 and 576 g a.i./ha under test conditions.